Interest in Gamification Learning Based on Student Learning Styles - Farman Farman; Chairuddin Chairuddin; Marniati Marniati (USN Kolaka, 2021)
This study aims to analyze student interest in gamification-assisted learning in terms of student learning styles. This research is a type of descriptive research using a qualitative approach. The subjects are students of the Mathematics Education Study Program, Faculty of Teacher Training and Education, USN Kolaka, a research course program with 20 students. The data collection technique used in this research is to use a questionnaire. The instrument used in this study was a questionnaire of learning styles and interest in learning in gamification-assisted learning. According to Miles and Huberman, the data analysis technique used in this study is a qualitative data analysis technique, namely data reduction, data presentation, and conclusion drawing. The results showed (1) the average student interest in gamification-assisted learning with word walls was in the high category, (2) student learning styles in research subjects mostly tended to be multimodal (60%), and (3) students with unimodal learning styles have high interest, bimodal, and trimodal learning styles have a very high interest in learning with gamification-assisted learning.